Fibrous Dysplasia of Skull: An Uncommon Presentation - Sethia, Madhuri; Siddiqui, Bushra; Rafey, Mohd; Khan, Arshi; Hasan, Mahboob (Annals of Pathology and Laboratory Medicine, 2025)
Fibrous dysplasia is a developmental disorder of bone that can occur in monostotic or polyostotic form. Monostotic form is more frequent, usually seen in older children and young adults, commonly occurring in ribs, femur, tibia and craniofacial bones. Polyostotic fibrous dysplasia is less common, affecting as few as two bones to as much as 75% of the skeleton, predominantly involving the femur, pelvis and foot. We present a case of fibrous dysplasia involving the skull in a 29-year-old woman. On magnetic resonance imaging (MRI), a well-defined lytic lesion was identified in the outer cortex of the left parietal lobe for which two differential diagnoses were made: Langerhans cell histiocytosis (LCH) and lymphoma. The patient underwent craniotomy followed by mesh cranioplasty. The atypical location of the lesion initially obscured the diagnosis, which was ultimately confirmed through histopathological analysis.